KEPEMIMPINAN KEPALA SEKOLAH DALAM MEMPERSIAPKAN KOMPETENSI GURU PENDIDIKAN AGAMA ISLAM DI SEKOLAH MENENGAH PERTAMA NEGERI 16 KOTA JAMBI - Juliana, Rachmawati (Journal of Applied Transintegration Paradigm, 2026)
This study aims to analyze the role and leadership strategies of school principals in preparing and enhancing the competencies of Islamic Religious Education (IRE) teachers at SMP N 16 Kota Jambi. The method employed is a qualitative approach, utilizing data collection through in-depth interviews, direct observations, and document studies. The findings indicate that school principals play a crucial role in addressing various challenges faced by IRE teachers, including resource limitations, time constraints, and administrative demands that often disrupt the teaching process. The principals implement several innovative strategies to improve teacher competencies, such as providing alternative training, developing relevant curricula, and more efficient distribution of administrative tasks. Additionally, reward programs for teachers who demonstrate excellence are also implemented as motivation to encourage professional development. These findings highlight that strong support from principals, along with active collaboration between teachers and school stakeholders, is essential for creating a conducive environment for the development of IRE teacher competencies. This research provides recommendations to enhance support in teacher training programs and reduce administrative burdens, thereby improving the overall quality of IRE education. Consequently, the results of this study are expected to serve as a reference for school principals and policymakers in efforts to enhance the quality of education in schools.